2009
DOI: 10.1002/bsl.860
|View full text |Cite
|
Sign up to set email alerts
|

Non‐invasive brain stimulation in the detection of deception: Scientific challenges and ethical consequences

Abstract: Tools for noninvasive stimulation of the brain, such as transcranial magnetic stimulation (TMS) and transcranial direct current stimulation (tDCS), have provided new insights in the study of brain-behavior relationships due to their ability to directly alter cortical activity. In particular, TMS and tDCS have proven to be useful tools for establishing causal relationships between behavioral and brain imaging measures. As such, there has been interest in whether these tools may represent novel technologies for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 85 publications
0
27
0
Order By: Relevance
“…For example, Lubner's group (described in Luber et al, 2009) performed a single-pulse TMS study in which stimulation was delivered over a series of intervals between 0 and 480 ms after stimulus presentation in a playing-card GKT paradigm. Based on previous results, they applied stimulation over left DLPFC, with stimulation of parietal precuneus cortex as a control.…”
Section: Causal Results From Loss-of-function Studiesmentioning
confidence: 99%
“…For example, Lubner's group (described in Luber et al, 2009) performed a single-pulse TMS study in which stimulation was delivered over a series of intervals between 0 and 480 ms after stimulus presentation in a playing-card GKT paradigm. Based on previous results, they applied stimulation over left DLPFC, with stimulation of parietal precuneus cortex as a control.…”
Section: Causal Results From Loss-of-function Studiesmentioning
confidence: 99%
“…Other emerging methods that have the potential to manipulate memories include minimally invasive brain stimulation techniques such as Transcranial Magnetic Stimulation (TMS) and transcranial Direct Current Stimulation (tDCS) (George et al 2009;Luber et al 2009;Sparing and Mottaghy 2008). These methods stimulate the brain either by inducing an electrical field using a magnetic coil placed against the head (TMS), or by applying weak electrical currents via electrodes on the scalp (tDCS) (Nuffield Council on Bioethics 2013).…”
Section: External Methodsmentioning
confidence: 99%
“…In the case of TMS, studies have shown improved performance in various complex motor learning tasks Kobayashi et al 2004), language-related abilities (Mottaghy et al 1999), visuospatial processing (Hilgetag et al 2001;Walsh et al 1998), perceptual abilities (Gallate et al 2009;Snyder et al 2003Snyder et al , 2006Snyder 2009) and in modulating social cognition (Knoch et al 2006;Lo et al 2003;Luber et al 2009;Young et al 2010). Regarding tDCS, there are studies suggesting that it enhances working (Fregni et al 2005;Ohn et al 2008) and declarative (Marshall et al 2004) memory as well as certain forms of learning (Bullard et al 2011;Flöel et al 2008).…”
Section: Brain Stimulationmentioning
confidence: 95%